Ligand-based homology modelling of the human CB2 receptor SR144528 antagonist binding site: a computational approach to explore the 1, 5-diaryl pyrazole scaffold. Issue 11 (28th September 2015) - Cichero, Elena; Menozzi, Giulia; Guariento, Sara; Fossa, Paola
Abstract : SR144528 docking mode into the LBHM of the human CB2 receptor antagonist binding site. Abstract : CB1 and CB2 receptors belong to the large family of G-protein coupled receptors (GPCRs), being involved in a wide variety of signal transduction processes. In this context, CB2 selective compounds were described in the literature to be active in different neuropathic and inflammatory pain models, also showing beneficial effects as neuroprotective agents. Indeed, CB2 proved to be up-regulated in reactive microglial cells in Alzheimer's disease (AD) and Huntington's, suggesting a promising therapeutic panorama for CB2 inverse agonists/antagonists. At present, the development of new selective CB2 antagonists is prevented by an unclear depiction of the reference antagonist SR144528 binding mode. Indeed, a few number of models concerning the CB2 receptor antagonist binding site have been proposed, leading sometimes to contradictory results. In this context, a specific h CB2 ligand-based homology model in the presence of the antagonist SR144528 was built. Notably, the refined model also allowed us to explore the pyrazole scaffold as prototype for CB2 ligand recognition and also to elucidate the CB1 /CB2 structure–activity relationship of an in-house series of analogues we previously published. The derived information is expected to be a useful tool for guiding a much more focused and reliable CB2 antagonist design.